Relations between Parenting and Adolescents’ Academic Functioning: The Mediating Role of Achievement Goal Orientations - Xu, Xinpei; Dai, David; Liu, Ming; Deng, Ciping (Frontiers in Education, 2018)
We investigated whether and how adolescents’ perceived parental psychological control and autonomy support influence their maladaptive academic functioning through their achievement goal orientations. Participants were 845 tenth-grade students (447 boys, Mage = 15.20 ± .54 years; 398 girls, Mage = 15.13 ± .47 years) in China. Data were collected on their reported achievement goal orientations, perceived parental psychological control and autonomy support, and academic-related beliefs, strategies, and behaviors. Bootstrapping with resampling strategies was used for testing multiple mediators’ model and examining mediation effect. Results indicated that, compared with girls, adolescent boys perceived higher parental psychological control. Moreover, we found distinct effects of parental psychological control and autonomy support on adolescents’ maladaptive academic functioning through achievement goal orientations. Specifically, parental psychological control led to adolescents’ maladaptive academic functioning, mainly through adolescents’ performance-approach goal orientation (.06, BC 95% CI [.03, .09]) and performance-avoidance goal orientation (.02, BC 95% CI [.01, .03]) rather than mastery goal orientation (-.00, BC 95% CI [-.01, .01]); while parental autonomy support reduced adolescents’ maladaptive academic functioning, mainly through their mastery goal orientation (-.02, BC 95% CI [.11, .19]) rather than performance-approach goal orientation (.01, BC 95% CI [-.01, .03]) and performance-avoidance goal orientation (.01, BC 95% CI [-.01, .02]). The results suggest that adolescents will benefit from parents ameliorating maladaptive academic functioning through fostering mastery goal orientations, and be harmed from parents facilitating maladaptive academic functioning through enhancing performance-approach and performance-avoidance goal orientations.